The effect of family empowerment training based on self-compassion on self-care and fasting blood sugar in female patients with type 2 diabetes - Pakravan Bahri, Farideh; Ahmadi Tahour Soltani, Mohsen; Ghorban Shiroudi, Shohreh (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The purpose of this research was to determine the effect of family empowerment training based on self-compassion on self-care and fasting blood sugar in female patients with type 2 diabetes. Method: In a randomized clinical trial study with a control group and pre-test and post-test, 60 women with type 2 diabetes who referred to the endocrinology department of Imam Hossein (AS) hospital located in Tehran province in Fall 2021 were selected by random sampling method. became Then the subjects were randomly assigned in two experimental and control groups through Excel office software. The experimental group (n=15) (under self-compassion-based family empowerment training for 8 weekly sessions of 90 minutes each session) and the control group (n=15) underwent routine hospital training. The data collection tool of diabetes self-care scale questionnaire and fasting blood sugar were collected in three stages of baseline, after intervention and three-month follow-up. The data was entered into SPSS statistical software version 21 and analyzed using multivariate repeated measure analysis of variance. Results: The findings showed that in the group under family empowerment training based on self-compassion, the average score of self-care is significantly higher than the control group. In addition, women with diabetes in the experimental group decreased significantly in the average fasting blood sugar score compared to the control group (P < 0.001). Conclusion: The results of this research showed that teaching the family empowerment model based on self-compassion can be effective in improving self-care and reducing fasting blood sugar in women with type 2 diabetes.